Combined impact of future trends on healthcare utilisation of older people: A Delphi study. Issue 10 (October 2019) - Ravensbergen, W.M.; Drewes, Y.M.; Hilderink, H.B.M.; Verschuuren, M.; Gussekloo, J.; Vonk, R.A.A.
Highlights: Previous studies on future healthcare utilisation only consider the effect of single trends. This work explores the effect of interaction between trends on healthcare utilisation. The expected extra increase of healthcare use by older people emphasises the need to include interaction in foresight studies. Abstract: Purpose: To explore the combined effect of trends in older people on their future healthcare utilisation. Methods: A Delphi study consisting of two rounds was conducted. The heterogeneous expert panel (n = 16) in the field of elderly care rated the effect of combinations of trends in the Netherlands on the use of seven healthcare services: i.e. informal, home, general practitioner, acute, specialist, nursing home and mental health care. The percentage and direction of the overall consensus, for the different health services, and for three main trends were analysed. Results: Experts reached consensus in 57 of 92 ratings (62%). Taking into account the interaction between trends, they expected an extra increase for informal, home, and general practitioner care, but no additional effect of interaction for specialist and acute care. Combinations that included trends leading to less support were expected to lead to an extra increase in utilisation. Conclusions: Experts expect that interaction between trends will lead to an extra increase in the use of general practitioner, home, and informal care. This increase is mainly the result of interaction with trends leading to less support for older persons. The present results show the need to take the effect of interaction into account when designing new health policy and in research on future healthcare utilisation.